The Ecomaterialist Appropriation of the Shakespearean Stage: Tracing the Entangled Worlds in Rupert Goold's The Tempest (2006) - Gulter, Isil Sahin (Istanbul Univ, Fac Letters, 2024)
Contemporary environmental concerns and ecological issues stimulate updated adaptation and appropriation of dramaturgy, allowing the playwrights, directors, stage designers, and performers to reconsider conventional strategies of theatre. Pushing intellectual and creative boundaries, the material-based practice of ecological theatre has recently found expression in theatre and performance studies. Drawing mainly upon recent ecomaterialist notions, this paper traces the entanglement of the material worlds in Rupert Goold's The Tempest (2006). Therefore, this paper aims at investigating how Goold reappropriates the stage by employing William Shakespeare's canonical text under the specific conditions of the Anthropocene, directly depicted on stage through arctic scenery, shipwreck, storm, and human despair against nonhuman climatic forces. By analyzing the 2006 production of The Tempest from an ecomaterialist point of view, this paper indicates that Goold pays particular attention to the entanglement of humans and more-than-human worlds, fostering the idea that a human being is an integral component of the material environment that contains and sustains, rather than being a distinct entity. Thus, by assigning distributive agency to the matter on stage, Goold uncovers nonhuman performance and suggests that each performing actor uniquely participates in the process of meaning and affect.
Keywords: The Tempest; Rupert Goold; the Anthropocene; Ecomaterialist Theatre; Material Entanglement